Penerapan Ketentuan Pidana bagi Penyelenggara Jalan yang Mengakibatkan Terjadi Kecelakaan - Kotta, Ridjal Junaidi; Syafari, Tri (Khairun Law Journal, 2018)
The implementation of criminal provisions for Road operators which resulted in accidents in South Halmahera District is not effective because until now there has been no complaints / reports and demands from the community to the South Halmahera Resort Police related to traffic accidents due to damaged roads. This is because the public does not understand the existing rules (criminal provisions in Article 273 of Law Number 22 Year 2009) due to lack of socialization and legal counseling to the public. Community ignorance of existing rules (criminal provisions in Article 273 of Law Number 22 Year 2009) and the non-proactive role of the police in following up on traffic accidents experienced by the community due to damaged roads and lack of socialization and legal counseling by the government to Public.